Secondhand tobacco smoke exposure and sleep disturbance in school-aged children in Appalachian Ohio - McWhorter, Ketrell; Kim, Christine; Hilbert, Timothy J.; McBride, Danielle E.; Mangino, Anthony A.; Parsons, Patrick J.; Kannan, Kurunthachalam; Haynes, Erin N. (Frontiers in Pediatrics, 2025)
IntroductionSecondhand tobacco smoke (SHS) exposure remains a major public health concern for children and has been implicated in sleep disturbances through biological and behavioral mechanisms. Different methods of measuring SHS exposure have yielded inconsistent results. This study examined the relationship between SHS exposure and sleep among rural Appalachian 7–9-year-olds, utilizing three SHS measurements: natural log-transformed (ln) serum cotinine concentrations, dichotomized serum cotinine levels (≥0.05 vs. <0.05 ng/ml), and parent/caregiver report of ≥1 smoker in the home. We hypothesized SHS-exposed children would have a significantly higher prevalence of sleep disturbance—e.g., short sleep, frequent snoring, night awakenings—compared to unexposed, regardless of measurement method.MethodsWe used data from the Marietta Community Actively Researching Exposure Study, a cohort of 404 children in Marietta and Cambridge, Ohio. Sleep disturbances were parent/caregiver-reported. Linear models were used for continuous outcomes to estimate beta coefficients; log-binomial models with generalized estimating equations (exchangeable correlation) were applied for dichotomized outcomes to estimate prevalence ratios (PR), each with 95% confidence intervals (CI).ResultsTwenty-six percent of children had a parent/caregiver report of ≥1 sleep disturbance. There was a 35% increased prevalence of short sleep [PR = 1.35 (95%CI:1.02–1.80), p = .04] with each unit increase of ln serum cotinine levels, adjusting for age, sex, parent education, BMI percentile, and history of breathing difficulties in the past two years. Increasing ln serum cotinine levels were associated with a significant 5.5-min decrease in average sleep duration in age-adjusted models.ConclusionsHigher SHS exposure was associated with poorer sleep outcomes, with serum cotinine emerging as the only measure linked to short sleep, underscoring the importance of smoke-free environments, particularly in rural communities, and objective exposure assessment.